The Influence of The Problem Based Learning Model to Improve Student Learning Outcomes on Newton's Law Material at SMA Negeri 1 Percut Sei Tuan - Pasaribu, Shofia Debora; Derlina (Physics Education Research Journal, 2025)
This study aims to determine whether the influence of problem-based learning models can improve student learning outcomes in the main material of Newton's law in the even semester of class X of SMA Negeri 1 Percut Sei Tuan. This study is a quasi-experimental study. The population of the study was all students of class X of SMA Negeri 1 Percut Sei Tuan consisting of 10 classes, then sampling was carried out using random sampling techniques. The instrument used to determine student learning outcomes was a learning outcome test in the form of a multiple-choice test totaling 20 questions. The results of the study obtained an average pretest score of the experimental class of 34.58 and a control class of 32.77. After the pretest data was normal and the difference test was homogeneous, the values ​​of the two classes were obtained that both classes had the same initial abilities. Then different treatments were given, namely the experimental class with a problem-based learning model and the control class with a conventional model. The average posttest score of the experimental class was 81.66 and the control class was 65.69. After the normal and homogeneous posttest data were obtained, the difference test values ​​of the two classes showed that there were differences due to the influence of the problem-based learning model on student learning outcomes in the main material of Newton’s law in class X of SMA Negeri 1 Percut Sei Tuan.